Elucidating the therapeutic potential of Q8 in Glioblastoma Multiforme - Lonergan, Sean (Trinity College Dublin. School of Medicine. Discipline of Physiology, 2024)
Glioblastoma multiforme (GBM) is the most common and aggressive form of brain cancer in humans. Despite advancements in treatment and care, patient outcomes and survival rates are abysmal, with a five-year survival rate of 6.8%. In addition, treatment resistance and tumour recurrence are major contributing factors to GBM severity. Novel therapeutic strategies are urgently needed to combat these issues. Anti-angiogenic drugs reduce the formation of blood vessels by tumours which in turn cuts off blood and nutrient flow and can limit growth and invasion. 1,4-dihydroxy quininib, (Q8), is a novel anti-angiogenic molecule with proven efficacy in other hard-to-treat cancers and here we will test its utility in GBM. Natural killer (NK) cells are a highly specialised innate immune cell that target cancer cells and exhibit a potent anti-tumour response. Here, we showed the ability of Q8 to decrease GBM cell viability in the U251 GBM cell line model at doses above 10μM. In addition, Q8 displayed potent immunostimulatory activity, most notably in the promotion of IL-2 secretion. Finally, we demonstrated Q8’s ability to enhance expression of activating NK receptor ligands MICA/B and B7-H6 on U251 and T98G GBM cells, eluding to its potential use in combination with NK cell-based therapies. Interestingly, Q8-treated GBM cell supernatants also enhanced activating NK receptor Nkp46 and activation marker CD69 on NK cell therapy KHYG-1 cells, indicating an immunostimulatory effect on NK cell function and is in line with the drug’s induction of IL-2 in GBM cells. In contrast, Q8 increased inhibitory NK receptor ligand HLA-E on GBM cell lines and therefore it’s cumulative effects on NK cell responses requires further investigation. Overall, our in vitro data suggests that Q8 elicits both direct and indirect anti-cancer effects in GBM and should be considered for further interrogation in ex vivo and in vivo models.
APPROVED
Keywords: Angiogenesis; Glioblastoma multiforme; NK-cell therapy